FRI0273 Rna sequencing detection of gene dysregulation in epithelial sorted cells from salivary gland tissue reveals interesting pathways involved in sjÖgren's syndrome pathophysiology. (12th June 2018) - Rivière, E.; Tchitchek, N.; Nocturne, G.; Boudaoud, S.; Pascaud, J.; Virone, A.; Thai, A.; Allaire, N.; Jagla, B.; Mingueneau, M.; Mariette, X.
Abstract : Background: Primary Sjögren's syndrome (pSS) is a chronic autoimmune disorder characterised by lymphocytic infiltrates and destruction of the salivary glands. Several lines of evidence support the hypothesis that salivary gland epithelial cells (SGECs) are not only the target of autoimmunity in pSS patients but may also play a role for its initiation and maintenance. Objectives: To establish high-resolution molecular maps of SGEC from pSS patients compared to controls using RNASeq analysis. Methods: Patients had pSS according to 2016 EULAR/ACR criteria and controls had sicca symptoms without any antibodies and with normal lip biopsy. SGEC, B, T CD4 and CD8 lymphocytes were sorted from salivary gland biopsies from 9 pSS patients and 4 controls, using a FACS ARIA cell sorter. Total RNASeq profiling was performed using MiSeq (Illumina). For SGEC subset, 4 samples were excluded due to a contamination by B lymphocytes, thus analysis was performed on 5 pSS and 4 controls using R software, to identify transcriptional differences between pSS and control SGEC. Functional Enrichment analysis was performed using Ingenuity Pathway Analysis software. Results: In SGEC, 495 genes were differentially expressed between pSS and controls. 280 genes were up-regulated, and 215 genes were down-regulated. Enrichment analysis (table 1 ) highlighted IL-7 signalling pathways (including IL-7, STAT5A, STAT1 genes) and interferon signalling (including OAS1, IFIT3, IFI6, TAP1 genes). Other genes potentially involved in immune responses and interactions between SGEC and lymphocytes were significantly up-regulated, including bone marrow stromal cell antigen 2, HLA-DRA, BAFF-R and IL-23 A (table 2 ). These results need to be confirmed by RT qPCR. However, consistent results have already been obtained in our laboratory, showing that IL-7 serum level is increased in pSS patients compared to controls and that SGECs produce IL-7 after interferon stimulation. The analysis of the non-coding RNA part and the other sorted cells subtypes is ongoing. Conclusions: Immune interactions between SGEC and B or T lymphocytes could represent a key in the understanding of the initiation and/or maintenance of autoimmunity in pSS. Our study highlights the key role of epithelial cells in activation of immune cells. In vitro experiments are needed to confirm these results and elucidate the molecular mechanisms. Acknowledgements: Arthritis Fondation Courtin, Arthritis R and D for providing a PhD fellowship Disclosure of Interest: None declared